Variable transcriptional responsiveness of the P2X3 receptor gene during CFA-induced inflammatory hyperalgesia - Nuñez-Badinez, Paulina; Greffrath, Wolfgang; Treede, Rolf-Detlef (Journal of cellular biochemistry, 2018)
The purinergic receptor P2X3 (P2X3-R) plays important roles in molecular pathways of pain, and reduction of its activity or expression effectively reduces chronic inflammatory and neuropathic pain sensation. Inflammation, nerve injury, and cancer-induced pain can increase P2X3-R mRNA and/or protein levels in dorsal root ganglia (DRG). However, P2X3-R expression is unaltered or even reduced in other pain studies. The reasons for these discrepancies are unknown and might depend on the applied traumatic intervention or on intrinsic factors such as age, gender, genetic background, and/or epigenetics. In this study, we sought to get insights into the molecular mechanisms responsible for inflammatory hyperalgesia by determining P2X3-R expression in DRG neurons of juvenile male rats that received a Complete Freund's Adjuvant (CFA) bilateral paw injection. We demonstrate that all CFA-treated rats showed inflammatory hyperalgesia, however, only a fraction (14-20%) displayed increased P2X3-R mRNA levels, reproducible across both sides. Immunostaining assays did not reveal significant increases in the percentage of P2X3-positive neurons, indicating that increased P2X3-R at DRG somas is not critical for inducing inflammatory hyperalgesia in CFA-treated rats. Chromatin immunoprecipitation (ChIP) assays showed a correlated (R2 = 0.671) enrichment of the transcription factor Runx1 and the epigenetic active mark histone H3 acetylation (H3Ac) at the P2X3-R gene promoter in a fraction of the CFA-treated rats. These results suggest that animal-specific increases in P2X3-R mRNA levels are likely associated with the genetic/epigenetic context of the P2X3-R locus that controls P2X3-R gene transcription by recruiting Runx1 and epigenetic co-regulators that mediate histone acetylation.